Professional learning community, teachers’ self-efficacy towards teacher job satisfaction amongst teachers in physical education in Iraq - Mutsher, Fathil Bakir (2018)
The job satisfaction theory makes proposition that job satisfaction is the result of a person's success in performing the job, while the self-efficacy theory asserts that the success of a person in performing his duties is due to the high level of efficacy, and to increase the level of self-efficacy, teachers need to attend in-service training such as professional learning community (PLC) programme. However, past studies in Iraq failed to show that PLC is affected teachers' self-efficacy and job satisfaction, as well as teachers' self-efficacy as mediators for the relationship between PLC and teachers' job satisfaction. Therefore, this study was conducted to determine the relationship between PLC, teachers' self-efficacy and job satisfaction, and self-efficacy as mediator for the relationship between PLC and job satisfaction. A survey and correlational design was utilized involving 265 physical education teachers from four Iraq provinces selected randomly as respondents in this study. Three standardized questionnaires namely, Professional Learning Communities Assessment-Revised (PLCA-R), Physical Education Teachers' Physical Activity Self-Efficacy Scale (PETPAS), and Teaching Satisfaction Scale (TSS) were used to measure PLC, teachers' self-efficacy, and job satisfaction. All questionnaires were translated into Arabic language using back-translation method. Pilot study showed that the translated version of questionnaires was highly reliable. Pearson correlation and multiple regressions were used to test the hypotheses of the study. Result revealed that PLC was positively related with self-efficacy and job satisfaction. The study also found that self-efficacy was a significant mediator for relationship between PLC and job satisfaction. This study has contributed to the development of job satisfaction, teachers' self-efficacy, and PLC theories in the context of education sector in Iraq. This study recommends that in order to increase teachers' job satisfaction, teachers' self-efficacy need to heighten, and to increase the level of teachers' self-efficacy, PLC need to be conducted consistently.